EXPLORING PRE-SERVICE CHEMISTRY TEACHERS’ PROBLEM SOLVING SKILLS ON VOCATIONAL CONTEXT-BASED LEARNING - Antuni Wiyarsi; Muhd Ibrahim Damanhuri; Nur Fitriyana (Universitas Negeri Yogyakarta, 2020)
Problem-solving skill is an important component in achieving a successful 21st-century learning system. This research aimed to explore Pre-service Chemistry Teacher’ (PsCT’) problem-solving skill after CBL (Context-based learning) implementation with vocational case on petroleum and polymer topic of chemistry. A descriptive study on the CBL implementation was adopted in this research. The study focused on the exploration of PsCT’ problem-solving skill. Through convenient sampling technique, the sample covered a total of 34 PsCT (10 males and 24 females) who enrolled in vocational chemistry course were selected in this study. The data of PsCT’ problem-solving skill were collected through Rubric for Problem-solving skill (RPSS). There were four aspects of problem-solving skill used in this research, namely problems identification skills, information collection skills, skills to provide possible solution, and skills of communicating the possible solution. These data were analysed according to descriptive quantity and one-way ANOVA technique. Three open-ended questions were used to explore PsCT’s view about the relevance, usefulness, and effectiveness of the CBL implementation. There was a significant difference on PsCT’ problems solving skills among petroleum and polymer topic. The result of this study indicated that PsCT’ problem-solving skill still in sufficient category. Hence, these skills should be improved especially on the skills to analyse the problem comprehensively and make an appropriate conclusion. The PsCT have positive view toward CBL implementation about the relevance, usefulness, and effectiveness. The implementation of CBL with vocational case is promising since it could improve PsCT’ problem-solving skills.